RELIABILITY AND DISCRIMINANT VALIDITY OF THE RUSSIAN VERSION OF EUROPEAN SELF-CARE BEHAVIOUR SCALE IN CHRONIC HEART FAILURE - Yu. M. Lopatin; A. A. Grebennikova; Yu. L. Begrambekova (Российский кардиологический журнал)
Aim. To assess reliability and discriminant validity of the Russian version of European Scale of Self-care in patients with heart failure (HF).Material and methods. European Scale of self-help assessment in CHF was translated in Russian according to Brislin model by three not related translators. After discussion by the workgroup members, professional translator retranslated back it to English, and the result was agreed with the author of the score. Then, 95 patients were included with chronic HF (CHF) of various etiology, who responded the questions at admittance and discharge from cardiological departments. Cronbach alpha was used for analysis of intrinsic consistency of the score. Also discriminant validity was evaluated.Results. Edication of CHF patients led to decrease of the whole points summ from 27,7±6,6 at admittance to 15,8±4,5 by discharge event. Coefficient of intrinsic consistency Cronbach alpha of the Russian version of European Scale was 0,826. Absence of significant relation of total points summ from Kansas questionnaire for cardiomyopathy patients and Minnessota questionnaire of life quality in HF proved discriminant validity of the Russian version.Conclusion. Russian version of European Scale of Self-help for patients with HF is easy to use and convenient instrument, which might be helpful for clinical trials as for clinical practice.